Elafibranor interrupts adipose dysfunction-mediated gut and liver injury in mice with alcoholic steatohepatitis. (13th February 2019) - Li, Tzu-Hao; Yang, Ying-Ying; Huang, Chia-Chang; Liu, Chih-Wei; Tsai, Hung-Cheng; Lin, Ming-Wei; Tsai, Chang-Youh; Huang, Shiang-Fen; Wang, Ying-Wen; Lee, Tzung-Yan; Huang, Yi-Hsiang; Hou, Ming-Chih; et al.
Abstract: Background: Reversal of alcohol-induced peroxisome proliferator-activated receptor (PPAR) α (PPARα) and PPARδ dysfunction has been reported to decrease the severity of alcoholic steatohepatitis (ASH). Autophagy is essential for cell survival and tissue energy homeostasis. Emerging evidence indicates that alcohol-induced adipose tissue (AT) autophagy dysfunction contributes to injury in the intestine, liver, and AT of ASH. Methods: The effects and mechanisms of dual PPARα/δ agonist elafibranor on autophagy stimulation were investigated using mice with ASH. Results: C57BL/6 mice on ethanol diet showed AT dysfunction, disrupted intestinal barrier, and ASH, which was accompanied by alcohol-mediated decrease in PPARα, PPARδ, and autophagy levels in intestine, liver, and AT. Chronic treatment with elafibranor attenuated AT apoptosis and inflammation by restoration of tissue PPARα, PPARδ, and autophagy levels. In ASH mice, alcohol-induced AT dysfunction along with increased fatty acid (FA) uptake and decreased free FA (FFA) release from AT was inhibited by elafibranor. The improvement of AT autophagy dysfunction by elafibranor alleviated inflammation and apoptosis-mediated intestinal epithelial disruption in ASH mice. Acute elafibranor incubation inhibited ethanol-induced ASH-mice-sera-enhanced autophagy dysfunction, apoptosis, barrier disruption, and intracellular steatosis in Caco-2 cells and primary hepatocytes (PHs). Conclusion : Altogether, these findings demonstrated that the PPARα/δ agonist, elafibranor, decreased the severity of liver injury by restoration of alcohol-suppressed AT autophagy function and by decreasing the release of apoptotic markers, inflammatory cytokines, and FFA, thereby reducing intestinal epithelium disruption and liver inflammation/apoptosis/steatosis in ASH mice. These data suggest that dual PPAR agonists can serve as potential therapeutic agents for the management of ASH.